Activation of the ATF3 gene through a co-ordinated amino acid-sensing response programme that controls transcriptional regulation of responsive genes following amino acid limitation - Pan, Yuan-Xiang (Portland Press Ltd., 2006)
Expression of ATF3 (activating transcription factor 3) is induced by a variety of environmental stress conditions, including nutrient limitation. In the present study, we demonstrate that the increase in ATF3 mRNA content following amino acid limitation of human HepG2 hepatoma cells is dependent on transcriptional activation of the ATF3 gene, through a highly co-ordinated amino acid-responsive programme of transcription factor synthesis and action. Studies using transient over-expression and knockout fibroblasts showed that several ATF and C/EBP (CCAAT/enhancer-binding protein) family members contribute to ATF3 regulation. Promoter analysis showed that a C/EBP-ATF composite site at −23 to −15 bp relative to the transcription start site of the ATF3 gene functions as an AARE (amino acid response element). Chromatin immunoprecipitation demonstrated that amino acid limitation increased ATF4, ATF3, and C/EBPβ binding to the ATF3 promoter, but the kinetics of each was markedly different. Immediately following histidine removal, there was a rapid increase in histone H3 acetylation prior to an enhancement in ATF4 binding and in histone H4 acetylation. These latter changes closely paralleled the initial increase in RNA pol II (RNA polymerase II) binding to the promoter and in the transcription rate from the ATF3 gene. The increase in ATF3 and C/EBPβ binding was considerably slower and more closely correlated with a decline in transcription rate. A comparison of the recruitment patterns between ATF and C/EBP transcription factors and RNA polymerase II at the AARE of several amino acid-responsive genes revealed that a highly co-ordinated response programme controls the transcriptional activation of these genes following amino acid limitation.